Review: 'Utrecht, Caravaggio and Europe', Centraal Museum Utrecht, Utrecht, 16 December 2018 – 24 March 2019. Catalogue: Eds. Bernd Ebert and Liesbeth M. Helmus, Munich, 2018, 304 pages, hardback, ISBN: 978-3-77743133-8, £45.00. (2020) - Marinelli, Alice
No abstract available